The Background: An Embodied Reason of Coping in the World - Radman, Zdravko (Investigaciones Fenomenológicas, 2014)
This paper is motivated by the general idea that philosophical ambition to understand and define the human mind exclusively in terms of conscious, propositional, and deliberative behaviour cannot be adequate, for it leaves out great part of our mentality, which resides in the background. On a more specific plane it focuses on the background as a means of providing the cognitive organism with most plausible scenarios of reality, and prepares it for what appears most likely to be the case in the world, in an instant way and without engaging in contemplation. The background proves to be a powerful instrument of initiating guesswork and does it in automatic and effortless manner. In such a way this backgrounded “reason” acts ahead of actuality and drives our behaviour and modes of our coping in the natural, social, and cultural world in an implicit way, not available in the conscious foreground. Este artículo viene motivado por la idea general de que la ambición filosófica de definir y entender la mente humana exclusivamente en términos de comportamiento consciente, proposicional y deliberativo no puede ser adecuada, pues deja inexplicada gran parte de nuestra mentalidad, la cual reside en el trasfondo. Más específicamente, el artículo se centra en el trasfondo como medio para proporcionar al organismo cognitivo los escenarios más plausibles de la realidad, y prepararlo para lo que más probablemente sea el caso en el mundo, de forma instantánea y sin entrar en la contemplación. El trasfondo demuestra ser un instrumento poderoso a la hora de hacer conjeturas de una manera automática y espontánea. De esta forma, esta “razón” de trasfondo se anticipa en la práctica y conduce nuestro comportamiento y modos de habérnoslas con el mundo natural, social y cultural de forma implícita, no disponible en el primer plano conscien-te.